GOGOL'S CHARACTERS AND THE IMAGE OF N.V. GOGOL IN CONTEMPORARY SCIENCE FICTION - Kuchinsky A.Yu. (International Journal of Literature and Language Studies, 2026)
This article examines examples of the deconstruction of Gogol's text and the recreation of the image of N.V. Gogol in the works of contemporary Russian science fiction writers, reflecting, among other things, features of postmodernist poetics.